2014
DOI: 10.1111/fwb.12487
|View full text |Cite
|
Sign up to set email alerts
|

Ecological engineering and aquatic connectivity: a new perspective from beaver‐modified wetlands

Abstract: Summary Habitat fragmentation and wetland loss due to anthropogenic causes are usually attributed to physical modifications of the environment; however, the loss of key species can compound these impacts and further reduce the connectivity of aquatic ecosystems. Ecosystem engineers can play a critical role in modifying aquatic systems by altering the bed of ponds and streams, increasing water coverage and influencing biogeochemical processes within and adjacent to freshwater habitats. However, there is a pau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 44 publications
(108 reference statements)
0
73
0
1
Order By: Relevance
“…Another study (focusing on C. canadensis ), by Butler and Malanson (1995) suggests a lower, but still noteworthy value of 0.4 m 3 per burrow (Butler and Malanson, 1995). Similarly, in a study of C. canadensis in 16 US wetlands, it was found that the contribution of sediment from beaver canals to rivers was significant (Hood and Larson, 2014). The authors show that, over a 13 km 2 area in the Miquelon Lake Provincial Park, Canada, an estimated 22 315 m 3 of sediment was released into the watercourse.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another study (focusing on C. canadensis ), by Butler and Malanson (1995) suggests a lower, but still noteworthy value of 0.4 m 3 per burrow (Butler and Malanson, 1995). Similarly, in a study of C. canadensis in 16 US wetlands, it was found that the contribution of sediment from beaver canals to rivers was significant (Hood and Larson, 2014). The authors show that, over a 13 km 2 area in the Miquelon Lake Provincial Park, Canada, an estimated 22 315 m 3 of sediment was released into the watercourse.…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that there will be some sediment sourced from beaver building activity and within site erosion (Lamsodis and Ulevičius, 2012; de Visscher et al ., 2014; Hood and Larson, 2014). Sediment partitioning or source determination was not undertaken as part of this study.…”
Section: Methodsmentioning
confidence: 99%
“…This is because the bathymetric curve proved resilient to fluctuations in "elevation" inherent to the impounded land surface. Also, the dams, intricate canals and holes that beavers create in the areas they inhabit (Hood and Larson, 2015) do not warp the shape of the bathymetric curve enough that a power function becomes inappropriate to sufficiently describe it. However, it appears that volume estimations are more resilient to aberrations in the bathymetric curve than are area estimates.…”
Section: V-a-h Model Performance In Beaver Pondsmentioning
confidence: 99%
“…The dominance of channel engineering and associated loss of river ecosystems and river processes has been widely discussed in the literature (Downs and Gregory 2014;Palmer et al 2014;Hood and Larson 2015;Peipoch et al 2015;Everard et al 2018;Wohl 2018). The river engineers involved in water resources development projects often cite the need of providing increasing water demands to growing population, whereas river ecologists argue about the needs of the riverine ecosystem in wake of unsustainable water abstractions (Downs and Gregory 2014).…”
Section: Introductionmentioning
confidence: 99%